HUBUNGAN ANTARA TITIK DIDIH DENGAN PERSENTASE MASSA DARI BEBERAPA LARUTAN MADU ALAMI DAN MADU KOMERSIAL - Dede Suhendar; Afifah Tasdiq; Asep Supriadin; Yusuf Rohmatulloh (Jurnal Penelitian Hasil Hutan, 2025)
The traditional society’s need for natural honey cannot easily be met with the many alternatives to commercial honey today, but the consistency of traditional methods in determining the authenticity of natural honey has not been scientifically confirmed. This simple research aims to study the relationship between the boiling point and mass percentage of some dilute natural honey based on the basic idea of the colligative properties of the solution and its comparison with some commercial honey samples. Each honey sample (six samples of natural honey and six samples of commercial honey) was diluted with distilled water in various weight percentages of 2.5–15.0% (w/w), then the boiling points were determined in ambient temperature and pressure. By using polynomial regression of degree 3, it was found that all-natural honey solutions had a pattern of increasing boiling point with increasing weight percentage, with different curvature patterns approaching linear (R3Lin), logarithmic (R3Log), exponential (R3Exp), and sigmoid (R3Sig) like patterns. The results of the comparison with six commercial honey solutions, there are only two samples that have an increasing regularity pattern, the rest are like fluctuates and/or has no relationship. Based on these results, the natural honey solution still has a close consistency with the colligative properties of the concentrated solutions so that it can be recommended as a new method in determining the authenticity of honey that has not undergone further processing, remains simple, easy, and inexpensive for testing.